2010
DOI: 10.1007/s00148-010-0313-0
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic discrimination in the Greek housing market

Abstract: Field experiment, Ethnic discrimination, Housing discrimination, C93, J70, R21,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Moreover, Albanians have higher access to housing in areas closer to the Athens centre, suggesting the role of landlords in creating residential ethnic segregation. In addition, Drydakis (2011b) suggests that higher housing discrimination is observed in higher status areas. This outcome suggests that the existence of isolated and racially segregated housing may be a result of prejudice and/or negative stereotypes against Albanians.…”
Section: Acknowledgementmentioning
confidence: 93%
“…Moreover, Albanians have higher access to housing in areas closer to the Athens centre, suggesting the role of landlords in creating residential ethnic segregation. In addition, Drydakis (2011b) suggests that higher housing discrimination is observed in higher status areas. This outcome suggests that the existence of isolated and racially segregated housing may be a result of prejudice and/or negative stereotypes against Albanians.…”
Section: Acknowledgementmentioning
confidence: 93%
“…These pre-conditions are: the widespread acceptance of a positive multicultural ideology; relatively low levels of prejudice and discrimination, no specific intergroup hatreds; and a sense of attachment to, or identification with, the larger society by all groups. In Greece, Drydakis (2010Drydakis ( , 2011a and Drydakis and Vlassis (2010) found patterns of ethnic segregation and extensive discrimination in the labor and housing market that might jeopardise immigrants' integration. When the media occasionally bring to light conflicts between immigrants and Greeks, immigrants complain that they face prejudice, and nationals complain that quiet places turn into ghettos.…”
Section: B the Formation Of Identitymentioning
confidence: 99%
“…In Greece, the scarce economic studies suggest that immigrants face lower wages than natives; are segregated in low status occupations, and are discriminated against in the labor and housing market (Lianos et al, 1996;Demousis et al, 2010;Drydakis and Vlassis, 2010;Drydakis, 2010;Drydakis, 2011a). Unfortunately, however, ethnic identity and employment outcomes have not been subject to examination 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Albanian minority(Drydakis, 2011) and, more recently,Ausperg et al's (2017) experiment in Germany, published after Rich's review, revealed discrimination against the Turkish minority, especially among those of low socio-economic status. Results from Combes et al's (2017) experiment involving African immigrants in French apartment blocks are suggestive of 'neighbourhood discrimination' effects, meaning that landlords who own multiple residential units within one building are reluctant to cater to minorities in case doing so would impact negatively on the price of their remaining units.…”
mentioning
confidence: 99%